Pulses and likelihood of Fúquene Lagoon flood occurrence - Jimenez-Sanchez, Juan David; Villamizar-Martin, Jimmy; Zamudio-Huertas, Eduardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2018)
The Lagoon of Fuquene has been repeatedly affected for flood events in the last 20 years. Due to this affectation, populations adjacent to the lagoon have been harmed, causing additional alterations to the biodiversity and ecosystem. With the purpose of studying the historical flood events of the lagoon, the daily records of the water levels of the lagoon of Fuquene will be evaluated. Based on that analysis, the historical flood pulses, flood frequency, flood probability of permanence was found. It was detected that the highest levels in the lagoon coincide with the winter seasons, which are April, May, June, July, November and December. The highest historical levels were presented in 2006, 2010, 2011 y 2012. This information is provided with the objective of guiding the nearby community of the lagoon or decision maker (relevant entities) to know when and duration of a possible flood, and to allow generate contingency plans and land use planning.